PROBLEMS IN THE DEVELOPMENT OF LIFE INSURANCE IN UZBEKISTAN AND WAYS TO SOLVE THEM - Obiddin Toshmurzaevich Yuldashev (PT. Antis International Publisher, 2024)
This article analyzes the problems related to the development of life insurance in the national insurance market, shows ways to solve the problems, and develops proposals aimed at the rapid development of life insurance